2020
DOI: 10.3389/fphar.2019.01517
|View full text |Cite
|
Sign up to set email alerts
|

Pimozide Inhibits the Human Prostate Cancer Cells Through the Generation of Reactive Oxygen Species

Abstract: The United States Food and Drug Administration-approved antipsychotic drug, pimozide, has anticancer activities. However, the role of reactive oxygen species (ROS) in its effect on prostate cancer is not well-known. We examined cell proliferation, colony formation, migration, ROS production, and the expression of antioxidant-related genes after treatment of human prostate cancer PC3 and DU145 cells with pimozide. In addition, histopathology, ROS production, and superoxide dismutase (SOD) activity were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
(40 reference statements)
1
17
0
Order By: Relevance
“…The present study has identified the SNHG17/β-catenin/TCF axis in PCa tumor cells; however, the possibility that other mechanisms may also be involved cannot be excluded. For example, Kim et al ( 34 ) reported that pimozide repressed the proliferation of PCa tumor cell lines (PC3 and DU145) via the generation of reactive oxygen species (ROS). Takeuchi et al ( 35 ) also reported that ROS was associated with the proapoptotic activity of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has identified the SNHG17/β-catenin/TCF axis in PCa tumor cells; however, the possibility that other mechanisms may also be involved cannot be excluded. For example, Kim et al ( 34 ) reported that pimozide repressed the proliferation of PCa tumor cell lines (PC3 and DU145) via the generation of reactive oxygen species (ROS). Takeuchi et al ( 35 ) also reported that ROS was associated with the proapoptotic activity of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pimozide, an FDA-approved psychotropic drug, inactivated STAT5a and downregulated the expression of ABCB1, thus sensitizing MCF7/DOX cells to DOX in vitro and in vivo, providing a promising strategy for treating patients with chemoresistant breast cancer in the clinic. In fact, pimozide has been found to have antitumor activity mediated by suppressing STAT5 in various types of cancer (25,(42)(43)(44). In breast cancer, pimozide has also been proven to promote apoptosis by inhibiting RAN GTPase and AKT and to inhibit epithelial-mesenchymal transition and cell migration (45).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the efficacy of both Pimozide and Fluspirilene towards intracellular Mtb was inhibited by ROS/RNS inhibitors. Of these two diphenylbutylpiperidines, only Pimozide is known to induce ROS/RNS production and to inhibit the expression of antioxidant genes, like catalase, in vitro as well as in vivo [57,78]. Interestingly, similar to the results from Cai, Zhou [57], addition of n-acetyl-cysteine (NAC), a general ROS scavenger, partly inhibited the Pimozide induced increase in ROS/RNS levels by human macrophages, and reduced bacterial survival (Figure 5B and D).…”
Section: Discussionmentioning
confidence: 99%